Is enucleation followed by peripheral ostectomy and Carnoy’s solution application an adequate treatment for Odontogenic keratocyst? A case series with up to five years of follow up - Arya, Varun; Singh, Minerva; Rajeev Pandey; Sanjeev Kumar; Jingade Krishnajirao Dayashankara Rao; Santosh Mishra (Brazilian Dental Science, 2022)
Objective: To evaluate the treatment outcome of enucleation and peripheral ostectomy with the use of Carnoy’s solution for management of Odontogenic keratocyst. Material and Methods: 17 patients with OKC who reported from 2011 to 2015 were included. All the cases were treated by enucleation and peripheral ostectomy of 0.5mm followed by Carnoy’s solution cauterization for 4 minutes. All patients were followed up for 4-5 years. Results: All the cases were followed-up by using serial panoramic radiography and clinical evaluation at regular intervals. No recurrence was reported in any of the cases. Conclusion: Treatment of Odontogenic keratocyst by enucleation and 0.5mm of peripheral ostectomy, followed by Carnoy’s solution cauterization for 4 minutes is an effective treatment with zero recurrence rates for five years of follow-up. KEYWORDS Odontogenic keratocyst; Enucleation; Carnoy’s solution; Recurrence.